Plasma biochemistry, gene expression and liver histomorphology in common carp (Cyprinus carpio) fed with different dietary fat sources. (June 2020) - Eljasik, P.; Panicz, R.; Sobczak, M.; Sadowski, J.; Barbosa, V.; Marques, A.; Dias, J.
Abstract: Demand for omega-3 long chain polyunsaturated fatty acids has become global challenge for aquaculture and different components have been used to increase nutritional value of fillets. The aim of this study was to evaluate influences of feeds on zootechnical parameters, biochemical plasma parameters, expression of lipid-dependent genes, hepatocyte histomorphologies, and fatty acid profiles in common carp fillets. We compared a control diet (CTRL), mimicking a commercial feed formulation for common carp, with three diets containing blends of vegetable oils and a DHA-rich alga ( Schizochytrium sp.) included at 3.125% (CB1) or 1.563% (CB2), and 2.1% salmon oil (CB3). The study revealed no differences in final body weight of fish fed CB1-3 diets in comparison with significantly lower CTRL. Concentrations of all biochemical parameters in plasma increased gradually in fish fed CB1-3 diets when compared to CTRL diet, with exception of triacylglycerol levels. Expression of hepatic fas, elovl-5a and pparα genes increased significantly in fish fed CB1 and CB2. Additionally, eicosapentaenoic (EPA) and docosahexaenoic acid (DHA) accumulation in muscle tissue was directly proportional to the amounts supplied in the diets. Our study revealed that carp fillet profiles can be manipulated for DHA and EPA-contents using enriched diets, depending on the source of fat.